Economic and emission impacts of energy storage systems on power-system long-term expansion planning when considering multi-stage decision processes. (January 2021) - Larsen, Martín; Sauma, Enzo
Highlights: We assess the long-term impact of energy storage systems on total costs and CO2 emissions. We proposed an adaptive two-stage generation, storage, and transmission expansion planning model. Our model incorporates the flexibility of adjusting some investment decisions by utilities. Adjusting investments to long-term demand trends is crucial to correctly evaluate power markets. We show a counterexample where ESS can reduce total system costs, but increasing CO2 emissions. Abstract: Energy storage systems (ESS) are becoming a key component for power systems due to their capability to store energy generation surpluses and supply them whenever needed. However, adding ESS might eventually have unexpected long-term consequences and may not necessarily help in reducing CO2 emissions; mainly because they can store energy from any source and add some inefficiencies. Thus, it is important to accurately assess the impact they could have on the long-term prospects of the overall power system. In this work, those effects are assessed using a new adaptive two-stage generation, storage, and transmission expansion planning model, which includes constraints related to the system's flexibility, commonly disregarded in long-term expansion analysis. The effects of including an adaptive step in the proposed planning model, where investments can be adjusted to long-term demand trends, and those of including or ignoring ramp and reserve constraints are analyzed. The methodology is illustrated using a 45-bus representation of the Chilean power system. We use this case study to illustrate a counterexample where ESS can help reducing total system costs, but increasing CO2 emissions. We do not argue this would be mostly the case, but this counterexample helps to illustrate that this situation is possible. Likewise, we show that including the adaptive (two-step) approach significantly changes the generation and transmission expansion mix, as well as the emission levels. Finally, disregarding ramps does reduce total costs and slightly increases emissions in the Chilean case, but dismissing power reserves does not significantly affect the results.